Effects of the Level and Frequency of Fertilization with hen Droppings on Zooplanktonic Density and Growth Performance of Common Carp Post-Larvae (CyprinusCarpio) - Djikengoue, Kameni Patricia Linda; Mambe, Tameghe Flora; Kpoumie, Nsangou Amidou; Tonfack, Achile Peguy (International Journal of Aquaculture Research and Development, 2020)
Zooplankton production and growth performance of post-larvae of common carp according to the level and frequency of fertilization with chicken droppings were studied between May and October 2017 at the IRAD pisciculture station in Foumban. To this end, two doses of hen droppings, namely 450 g/m3 (D450) and 600 g/m3 (D600), were each applied at two application frequencies (weekly (F2) and bimonthly (F1)). Thus, 1200 post-carp larvae were distributed in 12 identical concrete tanks (1.2m x 0.75m x 1m) each filled with 400 liters of water. The 2 doses applied at 2 frequencies were applied randomly in the 12 tanks in a complete random device comprising 3 treatments and 2 repetitions. Six days after fertilization, each tank was sown with zooplankton at a density of 7 individuals per liter (ind/l). The loading was carried out 12 days after fertilization at a density of 100 ind/m2. The results show that regardless of the dose and the frequency of droppings applied, the production of zooplankton was optimal 10 to 12 days after fertilization. Considering the growth performance, the tanks receiving the 600 g/m3 dose every 2 weeks presented the highest significant values ​​(p <0.05). On the other hand, the survival rate (36% on average) was not significantly influenced (p˃0.05) by the dose and the frequency of fertilization. The 600 g/m3 dose applied every two weeks can be recommended for the rearing of post-larvae common carp.
Keywords: Fertilization dose; droppings; zooplankton; growth performance; survival; post-larvae; Cyprinus carpio.